Adaptasi Harimau Sumatera melalui Rekayasa Prostetik Wajah dalam Pembuatan Karya Rias Fantasi - Aini Anisyah; Trisnani Widowati; Novia Restu Windayani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The visual adaptation of the Sumatran Tiger into fantasy facial makeup art is a strategic alternative media for the conservation campaign of this endangered species. This study aims to describe and analyze the feasibility of a prosthetic fantasy facial makeup work that adapts the anatomical and aesthetic elements of the Sumatran Tiger. The type of research used is descriptive quantitative. The data collection technique was through a performance assessment test of the work. The research instrument was an assessment rubric validated by three experts using the Aiken's V index and its reliability was analyzed with Cronbach's Alpha (0.889). The results showed that the average content validity of the instrument was 0.859 (85.9%). The quality of the prosthetic fantasy makeup work obtained an average value of 88.89% which is included in the